Retorik pembujukan dakwah dalam lagu nasyid: Kajian terhadap lagu Opick dan Hafiz Hamidun / Nur Sakinah Sabari - Nur Sakinah , Sabari (2018)
Implementation of daawah today needs a creative approach. One of the approach that can be used is metode through songs. Entertainment is a fitrah that loved by people. Islam does not ban entertainment but allow it with guidelines. As long as it suit with fitrah and comply with islamic law. Therefore, one of the entertainment form that get the most attention from audiences is songs. This study is about the concept of persuasion rhetoric in Islamic song selected. Other than that, the study focus at the analysis persuasion rhetoric through Islamic song selected. The study used method of content analysis from the album The Best Of Opick songs (2011) and I Love Rasulullah by Hafiz Hamidun. There are daawah message about faith, sharia and morality that applied in both album that found in the study. Example of daawah persuasion rhetoric that used in these album is through the good examples delivered directly and indirectly.